Legal Responsibility for The Notary in Creating The Coppie Collationee for Sale and Purchase Deals Before The Officer of Land Asset Concerning Land Registration Land with Notary Office and Government Regulation Number 24 of 1997 Concerning Land Registrati - Denny Tyas Saputra; Moediarti Trisnaningsih; Dewy Nelly Yanthy (International Journal of Latin Notary, 2021)
Notary or Land Deed Making Official (PPAT) is a public official who has an important role in ensuring legal certainty, order and legal protection through authentic deeds drawn up by and before him. In practice, there is a problem, namely the existence of a dispute over the transfer of land rights, where there are two parties claiming to be the owner of the same land object. Each party claims to be the owner because they have bought from the heirs of the original owner of the land. One party bases ownership because it has proof of the Sale and Purchase Deed that has been made by PPAT, while the other party bases it on the proof of the Coppie Collationnee Sale and Purchase Deed. Based on these problems, it is necessary to conduct research regarding the legal position of the Copie Collationnee made by the Notary on the Sale and Purchase Deed which is used as proof of ownership of land rights and what is the legal responsibility for the Notary who has made the Copie Collationnee on the Sale and Purchase Deed made before PPAT. The method used is descriptive analysis with a normative juridical approach. The research stage uses library research with secondary data and field studies with primary data. This data collection is obtained by means of document study and also interviews obtained by means of field studies. Furthermore, the data were analyzed using the juridical-qualitative method. The Notary Deed in the form of a Coppie Collationnee made on the Land Sale and Purchase Deed made by PPAT is a form of negligence from the Notary in making the deed, because it is not in accordance with Article 15 paragraph 2 letter c UUJN, so the position of the deed in the agreement is limited to a copy and is degraded into an agreement. under hand. As for the legal consequences of a notary's negligence in drawing up a deed, it may be subject to sanctions in accordance with Article 16 of the UUJN, namely in the form of written warning, temporary dismissal, respectful dismissal, or dishonorable discharge.